Cardiomyopathy associated with Ceutzfeld–Jakob disease: a diagnosis of exclusion: a case report. Issue 1 (17th January 2020) - Itzhaki Ben Zadok, Osnat; Orvin, Katia; Inbar, Edna; Rechavia, Eldad
Abstract: Background: Creutzfeldt–Jakob disease (CJD), the most common prion disease in humans, is primarily known for its adverse neurological impact and inevitable mortality. Data regarding myocardial involvement in CJD are scarce. Case summary: A 54-year-old female patient, presented with progressive effort dyspnoea, was diagnosed with unexplained non-ischaemic cardiomyopathy. An extensive cardiac work-up including cardiac magnetic resonance imaging (MRI) did not reveal any underlying aetiology. Simultaneously, the patient developed involuntary limb movements and progressive cognitive decline. Thalamic high-signal abnormalities on diffusion-weighted images were apparent on brain MRI. Based on these findings, she was subsequently referred to a neurology department, where she suddenly died the day after her admission. Brain autopsy demonstrated spongiform encephalopathy. A genetic analysis performed to her son revealed a mutation in the PRNP gene; all of these were consistent with CJD. Discussion: This case describes the clinical association of CJD and cardiomyopathy and the diagnosis prion-induced cardiomyopathy by exclusion. It is not inconceivable that the coexistence of these two clinical entities may be related to genetic expression and contemporaneously deposition of infectious prions in myocardial muscle and brain tissue. Awareness of this possible association could be of important public-safety concern, and merits further collaborative cardiac-neurological work-up to elucidate this phenotype among patients with unexplained cardiomyopathy with neurological symptoms that resemble CJD.